STRATEGI PENGEMBANGAN USAHA BATIK DI KAMPOENG JADOEL SEMARANG MELALUI DIGITAL MARKETING - Munifah Munifah; Edy Siswanto; Nindi Anggi Wardani; Suprapti Suprapti; Hendri Rasminto (Jurnal Padamu Negeri, 2024)
This community service aims to support the development of batik businesses in Kampoeng Jadoel, Semarang, through the implementation of digital marketing strategies. This activity is motivated by the challenges faced by batik MSMEs, such as limited market access, low digital literacy, and competition in the era of globalization. The implementation method includes digital literacy training, mentoring in creating marketing content, and optimizing the use of digital platforms such as social media, marketplaces, and websites. The results of the program show an increase in participants' understanding of the concept of digital marketing, the ability to utilize digital media for promotion, and an increase in sales of batik products. In addition, stronger branding and more interactive relationships with consumers are created. This program also provides recommendations for business sustainability, such as the development of an integrated digital marketing system and ongoing coaching. It is hoped that this service can be a model for community empowerment in supporting economic independence based on local wisdom.